Front Cover Picture: Rh‐Catalyzed Hydrogenation of CO2 to Formic Acid in DMSO‐based Reaction Media: Solved and Unsolved Challenges for Process Development (Adv. Synth. Catal. 2/2019). Issue 2 (14th December 2018) - Jens, Christian M.; Scott, Martin; Liebergesell, Bastian; Westhues, Christian G.; Schäfer, Pascal; Franciò, Giancarlo; Leonhard, Kai; Leitner, Walter; Bardow, André
Abstract : Thefront cover picture, provided by the teams of Bardow and Leitner, illustrates the interdisciplinary challenge for sustainable CO2 transformation ranging from the molecular transformation to the overall process design. The team of chemists and engineers exemplifies this for the catalytic hydrogenation of CO2 to formic acid, where the choice of the reaction medium is crucial both for catalyst performance and separation as well as for product isolation. More details on the solved and unsolved issues of the process concept under scrutiny are described in the full paper on pages 307–316 (C. M. Jens, M. Scott, B. Liebergesell, C. G. Westhues, P. Schäfer, G. Franciò, K. Leonhard, W. Leitner, and A. Bardow, Adv. Synth. Catal .2019, 361, 307–316; DOI:10.1002/adsc.201801098 ).